Building a Successful Family Business Board A Guide for Leaders, Directors, and Families - Pendergast, Jennifer M. (A Family Business Publication, 2011)
In Building a Successful Family Business Board , the authors show why private firms need the in-depth expertise and objective feedback that a well-chosen board, including qualified independent directors, can provide, and demonstrates how owners and directors can work together to ensure a long and profitable life for the firm.